Whitney Biennial : 2000 Biennial Exhibition. - Anderson, Maxwell L.; Auping, Michael; Cassel, Valerie; Davies, Hugh M.; Farver, Jane; Miller-Keller, Andrea; Rinder, Lawrence R.; Whitney Biennial 2000 (New York : Whitney Museum of American Art, 2000)
In this 2000 Biennial Exhibition catalogue, Whitney Museum director Maxwell L. Anderson explores the fascinating evolution of Whitney Biennials from 1932 to the present. The curators then ask in their introduction What have we learned about the art being created in the United States in this century turns ? The comprehensive artists' plate section includes more than 150 illustrations as well as explanatory texts that create a framework for understanding the vocabulary and meaning of current artistic enterprises. In addition, a valuable reference section at the end of the book offers biographical, bibliographical and exhibition data on each artist.
Adams, Dennis ; Aitken, Doug ; Amer, Ghada ; Amerika, Mark ; art-mark ; Bacher, Lutz ; Baldwin, Craig ; Baldwin, Lew ; Banerjee, Rina ; Baron, Rebecca ; Beecroft, Vanessa ; Belgum, Rolf ; Benjamin, Walter ; Benning, Sadie ; Bernat, Robin ; Besemer, Linda ; Bey, Dawoud ; Blake, Jeremy ; Booker, Chakaia ; Burns, M.W. ; Cai Guo-Qiang ; Calame, Ingrid ; Camnitzer, Luis ; Cohen, Jem & Fugazi ; Coplans, John ; Coyne, Petah ; Currin, John ; Day, E.V. ; Dial, Thornton ; Dingle, Kim ; Discenza, Anthony ; Donovan, Tara ; Dorsky, Nathaniel ; Drake, James ; Duncan, Theresa ; Erlich, Leandro ; Fakeshop ; Fischer, Vernon ; Frecon, Suzan ; Fridge, Brian ; Friedman, Dara ; Gibbons, Joe ; Gober, Robert ; Godmilow, Jill ; Goldberg, Ken ; Griffin, Kojo ; Grigely, Joseph ; Haacke, Hans ; Hancock, Trenton Doyle ; Havel, Joseph ; Huerta, Salomon ; Jafa, Arthur ; Joo, Michael ; Kauper, Kurt ; Kolbowski, Silvia ; Korine, Harmony ; Lawler, Louise ; Leitman, Ruth ; Lemieux, Annette ; Leveque, Les ; Lockhart, Sharon ; De Lottie, William ; Makepeace, Anne ; Manglano-Ovalle, Iñigo ; Marioni, Joseph ; McElheny, Josiah ; Mondini-Ruiz, Franco ; Morris, Errol ; Morrison, Mandy ; Muniz, Vik ; Neshat, Shirin ; Nicosia, Nic ; Pfeiffer, Paul ; Pope, Carl & Karen ; Ra'ad, Walid ; Ramirez Erre, Marcos ; Reeder, Jennifer ; Reid, Laurie ; Rosen, Kay ; Rovner, Michal ; De Salvo, Roman ; Sherwood, Katherine ; Simon, John F. Jr. ; Souza, Al ; Steinke, Darcey ; Subrin, Elisabeth ; Sullivan, Chris ; Sze, Sarah ; Tran, T. Kim-Trang ; Tuttle, Richard ; U'Dongo, Ayanna ; Verene, Chris ; Weintraub, Annette ; Welbon, Yvonne ; Wodiczko, Krzysztof ; Yanagi, Yukinori ; Yuskavage, Lisa
biog., ind. tent., gr. tent., bibliog. p. 226-258
Engels
Whitney Biennial : 2000 Biennial Exhibitions, Whitney Museum of American Art, New York, March 23 - June 4, 2000
boek